Militant memocracy in International Relations: Mnemonical status anxiety and memory laws in Eastern Europe. Issue 4 (12th October 2021) - Mälksoo, Maria
Abstract: This article theorises the nexus between mnemonical status anxiety and militant memory laws. Extending the understanding of status-seeking in international relations to the realm of historical memory, I argue that the quest for mnemonical recognition is a status struggle in an international social hierarchy of remembering constitutive events of the past. A typology of mnemopolitical status-seeking is presented on the example of Russia ( mnemonical positionalism ), Poland ( mnemonical revisionism ), and Ukraine ( mnemonical self-emancipation ). Memory laws provide a common instance of securing and/or improving a state's mnemonical standing in the relevant memory order. Drawing on the conceptual analogy of militant democracy, the article develops the notion militant memocracy, or the governance of historical memory through a dense network of prescribing and proscribing memory laws and policies. Similar to its militant democracy counterpart, militant memocracy is in danger of self-inflicted harm to the object of defence in the very effort to defend it: its precautionary and punitive measures resound rather than fix the state's mnemonical anxiety problem.